OS SINAIS NO EVANGELHO DE JOÃO: EXEGESE DE JOÃO 6.1-15 - Mantovani, José Pascoal (2013)
This tese will analyse the ocurrences of the word sign in the fourth gospel, having the exegesis of John 6. 1 - 15 as a paradigm - the multiplying of the loaves and fishes pericope. This pericope is in-serted within the Signs Book (chapters 1 - 12), which is marked by the ocurrance of seven signs, beign those: the Wedding at Cana (2. 1 - 11); the healing of the kings officer son (4. 43-54); the healing of the paralytic in Bethesda (5. 1 - 15); the multiplying of the loaves and fishes (6. 1 - 15); Jesus walking on the sea (6. 16 - 21); the healing of the man born blind (9. 1 - 41) and the resurrection of Lazarus (11. 1 - 45). Besides the narrative, semiotic and hermeneutical peculiarities the Gospel of John has, our research has revealed that the word sign frames the narrative, providing its structure and also providing John its cadence. We notice the tangency between dialogue and the signs, thus making the pericope at John 6. 1 - 15 exert a central role in the Passion Narrative - because it is intended as a readers identitary text, as well as for the Johannine community.